Factors Driving Unexpected Drought-Induced Nothofagus dombeyi Mortality in a Valdivian Temperate Rainforest, Argentina - Suarez, Maria Laura (2024)
Understanding the drivers of drought-induced tree mortality remains a significant scientific challenge. Here, we investigated an unexpected mortality event of Nothofagus dombeyi (Mirb.) Oerst. following the 2014–15 drought in a Valdivian rainforest, Argentina. Our focus was on long-term growth trend differences between vital and dead trees, and how the mixing of species in tree neighbourhoods drives tree growth during drought. The inter-annual variation of basal area increments of vital and 2014–15-dead N. dombeyi trees showed a similar pattern through the 1930–2015 period, while the climate–growth relationships indicated that precipitation during the growing season promoted growth in both vitality classes, regardless of whether they were in the wettest location. For the period 1990–2015, both vitality classes showed similar estimated growth regardless of competition level, whereas species mingling in the neighbourhood significantly affected the dead tree growth. Network analysis revealed that drought performance covaried positively with a neighbourhood dominated by species functionally different from the focal species only in vital trees. These findings suggest a nuanced response of N. dombeyi to drought, shaped by multifaceted interactions at both the individual tree and neighbourhood levels. This research underscores that species-specific relationships under different mixtures imply different tree responses within a stand, and add complexity to understanding drought response at the individual level.